Adoption of Augmented Reality (AR) in construction cost management: a preliminary framework - Azahari, Safiah; Che Haron, Roziha (Universiti Tun Hussein Onn Malaysia (UTHM), 2024)
The integration ofAugmented Reality (AR) into construction cost management practices has emerged as a promising technological advancementin the Architecture, Engineering and Construction (AEC) industry. However, despite its potential benefits, there existsanotablegap in understanding the practical application and barriersto implementingAR in this context. Therefore,to bridge this gap,thispaperdelves intothe conceptual foundationof AR to evaluate its potential implementationin construction costmanagement.This study aims to enlighten otherson the significance of innovative construction cost management practices. It will alsocontributetowardsin-depth knowledge ofthe role of AR inconstruction cost management.